Tolerance in Organ Transplantation: From Conventional Immunosuppression to Extracellular Vesicles - Monguió-Tortajada, Marta; Lauzurica-Valdemoros, Ricardo; Borràs, Francesc E. (Frontiers in Immunology, 2014)
Organ transplantation is often the unique solution for organ failure. However, rejection is still an unsolved problem. Although acute rejection is well controlled, the chronic use of immunosuppressive drugs for allograft acceptance causes numerous side effects in the recipient and do not prevent chronic allograft dysfunction. Different alternative therapies have been proposed to replace the classical treatment for allograft rejection. The alternative therapies are mainly based in pre-infusions of different types of regulatory cells, including DCs, MSCs and Tregs. Nevertheless, these approaches lack full efficiency and have many problems related to availability and applicability. In this context, the use of extracellular vesicles, and in particular exosomes, may represent a cell-free alternative approach in inducing transplant tolerance and survival. Preliminary approaches in vitro and in vivo have demonstrated the efficient alloantigen presentation and immunomodulation abilities of exosomes, leading to alloantigen-specific tolerance and allograft acceptance in rodent models. Donor exosomes have been used alone, processed by recipient antigen-presenting cells (APCs) or administered together with suboptimal doses of immunesuppressive drugs, achieving specific allograft tolerance and infinite transplant survival. In this review we gathered the latest exosome-based strategies for graft acceptance and discuss the tolerance mechanisms involved in organ tolerance mediated by the administration of exosomes. We will also deal with the feasibility and difficulties that arise from the application of this strategy into the clinic.